Correlation of rheumatoid and cardiac biomarkers with cardiac anatomy and function in rheumatoid arthritis patients without clinically overt cardiovascular diseases: A cross-sectional study - Duangkamol Aiewruengsurat; Thanyakamol Phongnarudech; Tippawan Liabsuetrakul; Thanapon Nilmoje (International Journal of Cardiology: Heart & Vasculature, 2023)
Background: Cardiac biomarkers have been shown to be related to cardiac abnormalities; nonetheless, few studies have confirmed the association between cardiac and rheumatoid biomarkers in rheumatoid arthritis (RA) patients. This study assessed the correlation of rheumatoid and cardiac biomarker levels with cardiac anatomy and function and explored the interaction between cardiac and rheumatoid biomarkers in RA patients without clinically overt cardiovascular diseases. Methods: A cross-sectional study was conducted among RA patients aged 18–65 years without other connective tissue diseases, overlap syndrome, heart disease, or renal failure were included. Main cardiac and rheumatoid biomarkers, including high-sensitivity troponin T (hsTropT), N-terminal pro-B-type natriuretic peptide (NT-proBNP), rheumatoid factor, and anti-cyclic citrullinated peptide antibody (ACPA), were collected. Echocardiography was performed to examine cardiac anatomy and function. Results: The mean left ventricular mass index (LVMI) was 80.8 g/sqm, and the relative wall thickness was 0.4. The mean left ventricular ejection fraction was 70.3%. The hsTropT levels showed a weak positive correlation with LVMI and E/e' ratio and a very weak correlation with E/A ratio. Interaction effect between hsTropT and ACPA on LVMI was found in univariate analysis, not in multivariate analysis. Higher systolic blood pressure (SBP) and the use of non-steroidal anti-inflammatory drug (NSAID) increased the LVMI. Only age was related to the E/e' increase. Conclusion: The effect of hsTropT on LVMI was probably modified by ACPA in RA patients without clinically overt cardiovascular diseases. Age, SBP, and NSAID use among RA patients should be taken into account due to their relations to cardiac abnormalities.